Recurrent Cholangitis with Congenital Hepatic Fibrosis and Pancreaticobiliary Maljunction after Roux-en-Y Reconstruction - Tokio Sugiura; Takeshi Endo; Koichi Ito; Kenji Goto; Yoko Sato; Satoshi Kondo; Tatsuya Suzuki; Takashi Hashimoto (Georg Thieme Verlag KG, 2013)
Abstract A 1-year-old girl had pancreaticobiliary maljunction, a choledochal cyst, and polycystic kidney. At the age of 4 years, she was treated by resection of the choledochal cyst and Roux-en-Y reconstruction because of the cyst's risk of cancer. She was diagnosed as having congenital hepatic fibrosis based on the histological findings. Postoperatively, she suffered recurrent fever of unknown origin, refractory to several antibiotics. At the age of 6 years, she underwent living donor liver transplantation from her father. Multi-drug-resistant Pseudomonas aeruginosa was cultured in the recipient's liver. After liver transplantation, she had no episodes of recurrent fever. Roux-en-Y reconstruction should be avoided for ductal plate malformations such as congenital hepatic fibrosis.